Listeria monocytogenes wall teichoic acid glycosylation promotes surface anchoring of virulence factors, resistance to antimicrobial peptides, and decreased susceptibility to antibiotics - Meireles, D (2020)
The cell wall of Listeria monocytogenes (Lm), a major intracellular foodborne bacterial pathogen, comprises a thick peptidoglycan layer that serves as a scaffold for glycopolymers such as wall teichoic acids (WTAs). WTAs contain non-essential sugar substituents whose absence prevents bacteriophage binding and impacts antigenicity, sensitivity to antimicrobials, and virulence. Here, we demonstrated, for the first time, the triple function of Lm WTA glycosylations in the following: (1) supporting the correct anchoring of major Lm virulence factors at the bacterial surface, namely Ami and InlB; (2) promoting Lm resistance to antimicrobial peptides (AMPs); and (3) decreasing Lm sensitivity to some antibiotics. We showed that while the decoration of WTAs by rhamnose in Lm serovar 1/2a and by galactose in serovar 4b are important for the surface anchoring of Ami and InlB, N-acetylglucosamine in serovar 1/2a and glucose in serovar 4b are dispensable for the surface association of InlB or InlB/Ami. We found that the absence of a single glycosylation only had a slight impact on the sensibility of Lm to AMPs and antibiotics, however the concomitant deficiency of both glycosylations (rhamnose and N-acetylglucosamine in serovar 1/2a, and galactose and glucose in serovar 4b) significantly impaired the Lm capacity to overcome the action of antimicrobials. We propose WTA glycosylation as a broad mechanism used by Lm, not only to properly anchor surface virulence factors, but also to resist AMPs and antibiotics. WTA glycosyltransferases thus emerge as promising drug targets to attenuate the virulence of bacterial pathogens, while increasing their susceptibility to host immune defenses and potentiating the action of antibiotics.